Excess visceral fat area as an independent risk factor for early postoperative complications in patients with obesity undergoing bariatric surgery - Han, Liping; Deng, Chaoyi; Zhao, Rui; Wan, Qianyi; Zhang, Xiaofang; Wang, Xiao; Chen, Yi (Frontiers in Endocrinology, 2023)
Background: Few studies have investigated the correlation between visceral fat area (VFA) and early postoperative complications in patients with obesity undergoing bariatric surgery. This study aimed to investigate the relationship between VFA and early postoperative complications in patients with obesity following bariatric surgery. Methods: The study was conducted at a tertiary university hospital. Patients with obesity who underwent laparoscopic sleeve gastrectomy between June 2016 and October 2020 were divided into two groups based on umbilical level VFA: high-VFA group (umbilical level VFA ≥ 100 cm2) and low-VFA group (umbilical level VFA < 100 cm2). Baseline characteristics, intraoperative and postoperative conditions, and early postoperative complications were compared between the groups. The primary outcome was early postoperative complications, and the secondary outcome was postoperative hospital stay. Results: The study included 152 patients, with 82 patients in the low-VFA group and 70 patients in the high-VFA group. The high-VFA group had a higher incidence of early postoperative complications (18.6 % vs. 3.7 %, P = 0.003) than the low-VFA group. The length of postoperative hospital stay did not differ significantly between the groups. Conclusions: Our study suggests that excess VFA is an independent risk factor for early postoperative complications following bariatric surgery, and VFA may be used in preoperative evaluations.